Model to control portioning for multi-component charge - Rybalchenko, M.O.; Selegej, A.M.; Golovko, V.I.; Selegej, S.M.; Mirgorodskaya, O.S. (Наука та інновації, 2020)
Introduction. Bell-less tops used in the charging area give significantly wider opportunities for regulating and distributing the charge material along the furnace top radius. Moreover, it becomes feasible to develop the methods for gas flow control and these methods shall differ from the conventional ones. One of such methods is introduction of multi-component portions of the charge with a technology based component ratio. Problem Statement. The bell-less top charging device is not designed for that type of portioning when the charge material mixing is accompanied with a simultaneous shift of one component with respect to other one for a certain set value, while charging. These portions can be formed with the use of computer-aided stock-conveying system, while discharging the material from weighing hoppers into the blast furnace conveyor. Purpose. This research aims at the development of the structure, the functioning algorithms and the mathematical model for the system to control the formation of multi-component mixed charge batches in order to increase the blast furnace productivity and to reduce the specific coke consumption. Materials and Methods. In this research, the methods of automatic control theory and artificial intellect for the synthesis of weight neuro-fuzzy controllers within the automatic control system of charge dosage have been used. The developed system designed to control multi-component charge portioning via PC has been tested by means of simulation modelling methods. Results. There has been developed an algorithm for operating the system for controlling the multi-component mixed charge preparation on the conveyor, given the arrangement of the specified components, their ratios in portions, total volumetric productivity of the conveyor, the variable geometry of the unloaded material, in the connection with the on-line information on the mixing process. The feasibility of the system has been verified by its simulation with the use of standard application tools. Conclusions. It has been established that the designed control system allows the formation of mixed portions of any composition defined by an operator at a given maximum output of the conveyor and prevents its overload in terms of mass or volume. Вступ. Застосування безконусних завантажувальних пристроїв значно розширило технологічні можливості регулювання і розподілу шихти по радіусу колошника доменних печей. При цьому виникла можливість розробки методів управління газовим потоком, одним з яких є завантаження в піч багатокомпонентних порцій шихти з технологічно обґрунтованим співвідношенням компонентів. Проблематика. Безконусний завантажувальний пристрій не призначено для формування порцій шихти шляхом змішування з одночасним зсувом в процесі завантаження одного виду матеріалу щодо іншого на задану величину. Реалізувати формування таких порцій можна за допомогою ЕО М системи шихтоподачі в процесі розвантаження матеріалів з вагових воронок на доменний конвеєр. Мета. Розробка структури, алгоритмів функціонування та математичної моделі системи управління формуванням багатокомпонентних (змішаних) порцій шихти для підвищення продуктивності доменної печі та зменшення питомої витрати коксу. Матеріали і методи. Використано методи теорії автоматичного управління і штучного інтелекту для синтезу нейронечітких регуляторів ваги для системи автоматичного регулювання дозування шихти. Застосовано методи імітаційного моделювання для тестування розробленої системи управління формування багатокомпонентних порцій шихти на ЕОМ. Результати. Розроблено алгоритм функціонування та виконано моделювання роботи системи управління формуванням змішаних порцій з урахуванням заданого розташування компонентів, їхнього співвідношення в порції, сумарної об'ємної продуктивності конвеєра, змінної геометрії сипучого матеріалу, що розвантажується з вагової воронки, у взаємозв'язку з оперативною інформацією про процес змішування. Висновки. Розроблена система управління дозволяє сформувати порції шихтових матеріалів відповідно до будь-якої структури при заданій максимальній продуктивності конвеєра, виключаючи його перевантаження за масою (об’ємом).